The Oxford handbook of economic conflict resolution - Bolton, Gary E.; Croson, Rachel T. A. (New York : Oxford University Press, 2012)
Individuals, groups, and societies all experience and resolve conflict. In this handbook, scholars from multiple disciplines offer perspectives on the current state and future challenges in negotiation and conflict resolution.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Conflict management